Wordsworth's ethics - Potkay, Adam, 1961- (Johns Hopkins University Press, 2013)
"Why read Wordsworth's poetry - indeed, why read poetry at all? Beyond any pleasure it might give, can it make one a better or more flourishing person? These questions were never far from William Wordsworth's thoughts. He responded in rich and varied ways, in verse and in prose, in both well-known and more obscure writings. Wordsworth's Ethics is a comprehensive examination of the Romantic poet's work, delving into his desire to understand the source and scope of our ethical obligations. Adam Potkay finds that Wordsworth consistently rejects the kind of impersonal utilitarianism that was espoused by his contemporaries James Mill and Jeremy Bentham in favor of a view of ethics founded in relationships with particular persons and things. The discussion proceeds chronologically through Wordsworth's career as a writer - from his juvenilia through his poems of the 1830s and '40s - providing a valuable introduction to the poet's work. The book will appeal to readers interested in the vital connection between literature and moral philosophy."--Project Muse.